Pathologically diagnosed early‐stage gastric adenocarcinoma with enteroblastic differentiation after endoscopic submucosal dissection: A case report - Hiroki Iwata; Hidehito Maeda; Kengo Tsuneyoshi; Takuma Matsumoto; Hiroshi Fujita; Yoshihiro Komohara; Akio Ido (DEN Open)
Abstract A 77‐year‐old male patient underwent esophagogastroduodenoscopy at his family doctor, and an easily hemorrhagic depressed lesion was noted near the anterior wall of the gastric antrum. A biopsy revealed moderately differentiated tubular adenocarcinoma > poorly differentiated adenocarcinoma, and the patient was referred to our department for further examination. A 15‐mm 0–IIc lesion is seen near the anterior wall of the gastric antrum and narrow band imaging magnifying endoscopy revealed obscured glandular duct structures and corkscrew pattern vascular structures. We diagnosed the patient with early‐stage gastric cancer [L, Ant, 15mm, cType0‐IIc, cT1(M‐SM1), cN0, cM0, cStage IA] after an esopahogastroduodenoscopy examination at our hospital, and endoscopic submucosal dissection was performed. Histopathological images with hematoxylin and eosin staining showed tumor cells with pale cytoplasm and the immunostaining for alpha‐fetoprotein, sal‐like protein 4, and Glypican3 was positive. The patient was pathologically diagnosed with gastric adenocarcinoma with enteroblastic differentiation, pT1b1 (SM, 0.4 mm), type 0–IIc, 15 mm, UL (‐), Ly0, and V0. Gastric adenocarcinoma with enteroblastic differentiation is one of the representative histological types of alpah‐fetoprotein‐producing gastric cancer. Alpha‐fetoprotein‐producing gastric cancer is infrequent, accounting for at least 3% of all gastric cancers, and is generally highly malignant. Most cases are already advanced upon diagnosis, and finding them in the early stage is rare. Therefore, pathological findings that may indicate the gastric adenocarcinoma with enteroblastic differentiation should be noted even in early gastric cancer.